2009
DOI: 10.1093/humrep/den387
|View full text |Cite
|
Sign up to set email alerts
|

Assisted reproductive technology and major structural birth defects in the United States

Abstract: These findings suggest that some birth defects occur more often among infants conceived with ART. Although the mechanism is not clear, couples considering ART should be informed of all potential risks and benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
206
6
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(235 citation statements)
references
References 28 publications
19
206
6
1
Order By: Relevance
“…More recently, a multicenter American case-control study has corroborated these observations (Reefhuis et al 2009). Nevertheless, none of the studies looked into a possible association between the administration of drugs used for ovarian stimulation and the incidence of congenital diseases.…”
Section: Perinatal Outcomesmentioning
confidence: 70%
“…More recently, a multicenter American case-control study has corroborated these observations (Reefhuis et al 2009). Nevertheless, none of the studies looked into a possible association between the administration of drugs used for ovarian stimulation and the incidence of congenital diseases.…”
Section: Perinatal Outcomesmentioning
confidence: 70%
“…In addition to maternal ethnicity and geographic location, previous studies have reported EA to be associated with maternal age (Leck et al, 1968;Harris et al, 1995), multiple gestation (Harris et al, 1995;Riley et al, 1998), infant sex (Robert et al, 1993) and use of assisted reproductive technology (Reefhuis et al, 2009). In a recent study of EA in the United States, women using assisted reproductive technology had a 4.5-fold increased risk of having an infant with EA (Reefhuis et al, 2009). Prevalence of EA has also been found to be higher among multiple births compared with singletons (Harris et al, 1995;Riley et al, 1998), and increased risk was reported with increasing maternal age (Leck et al, 1968;Harris et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the complications have been attributed to a higher frequency of multiple births and to the increased risk of premature delivery; however, other reports indicate that also singleton IVF children have a greater risk of low birth weight and of congenital anomalies [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%